Skepticism and nancial audit - Espinoza Huere, Florencio (2018)
The present research deals with the importance of the auditor to use the current philosophical skepticism in his professional audit work; The financial audit is a technical process performed by the public accountant, in the verification of the use of funds of an entity. The objective is to demonstrate to what extent skepticism will improve the financial audit. Method is the use of skepticism does it as a method and technique to find evidence. The population and sample: it is constituted by thirty public accountancy auditors, with intentional sample. Result: the thirty auditors surveyed represent 100%, twenty-eight responded that the auditor must have a skeptical attitude when plan and develop an audit, which represents 93%. Conclusion: i) it was demonstrated that the proper use of skepticism improves the level of financial audit ii) The current philosophical skepticism consists of a methodical doubt iii) It was shown that there is a relationship between skepticism and the financial audit.